Nasal congestion: algorithm for the diagnosis and treatment in children and adults - A. I. Kryukov (Медицинский совет, 2016)
Nasal congestion in adults and children remains a major challenge in otorhinolaryngology. Nasal breathing difficulty is one of the most common complaints of patients visiting otorhinolaryngologists. The main causes of nasal congestion are acute upper respiratory tract viral infections, manifested, for example, by acute rhinitis. [1]